Penerapan Kurikulum Merdeka dalam Pembelajaran Pendidikan Agama Islam melalui Metode Based Learning - Hanani, Hanif; Setyariza, Nur Ayu; Kusumawardani, Intan; Widayati, Sri Erna; Handayani, Yekti (Lembaga Yasin AlSys, 2024)
The independent learning curriculum is a learning curriculum that refers to a talent and interest approach. Curriculum plays an important role in education. Students will not achieve appropriate learning goals without an appropriate curriculum and teachers as facilitators have an important role in the ongoing learning process. The learning model as a basis for learning is considered to be able to help the continuity of learning because project-based learning (Project Based Learning) is an innovative learning model that focuses on students solving a problem by producing a product.